Hubungan Stress Kerja dan Konsumsi Makanan dengan Status Gizi Pegawai di Rumah Sakit Bhayangkara Denpasar - Parmini, Ni Putu Ary; Padmiari, Ida Ayu Eka; Tamam, Badrut (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2025)
Based on Riskesdas Bali based on occupational groups, data from Riskesdas in 2018, people in the employee profession experienced an increase in nutritional problems compared to 2013. The number of overweight people increased from 13.7% (2013) to 20.0% (2018), as well as with obesity increasing from 17.1% (2013) to 33.7% (2018). The World Health Organization (WHO) predicts that work stress will become a major threat to human health by 2020. The aim of this research is to determine the relationship between work stress and food consumption and the nutritional status of employees at Bhayangkara Hospital, Denpasar. The type of research used was Descriptive Analytical with a Cross Sectional survey method, with a sample size of 61 people, using the Chi-Square test. A total of 31 samples (50.8%) had normal nutritional status, with light work stress levels in 59 samples (96.7%). Most of the samples had energy consumption in the deficit category, 48 samples (78.7%), protein consumption in the adequate category, 26 samples (42.6%), fat consumption in the adequate category, 25 samples (41.0%) and carbohydrate consumption in the adequate category. deficit 57 samples (93.5%). There is no significant relationship between energy, protein, fat and carbohydrate consumption and work stress, shown by p 0.05. There was no significant relationship between energy, protein, fat and carbohydrate consumption and nutritional status, as shown by p 0.05.